Local television, citizen knowledge and political accountability: Evidence from the U.S. Senate - Nordin Mattias (Uppsala University, Department of Economics, 2015)
I investigate the causal effect of access to relevant local television on i) U.S. citizens' knowledge of their senators' actions in the Senate and ii) whether citizens hold their senators accountable for these actions. To do so, I utilize the mismatch between the local television markets and the states. This mismatch causes citizens living in counties where local television stations are based in their own state (in-state counties) to have greater access to relevant news about their senators, compared to citizens living in counties served by local television based in a neighboring state (out-of-state counties). Using survey data from the 2006 Cooperative Congressional Election Study, I find that the biased coverage of local television news leads to citizens in in-state counties, compared to out-of-state counties, to be more informed about their senators' roll-call votes, as well as more likely to hold opinions about these senators. However, I do not find that the increased knowledge affects the likelihood that citizens evaluate their senators based on the roll-call votes. This result suggests that passively acquired information through local television is not sufficient for individuals to hold their senators accountable for their actions in the Senate.
urn:nbn:se:uu:diva-264439
Keywords: D72; D80; H50; 330; local television; political information; natural experiment; roll-call votes